Integrating Mental Health Literacy in Maritime Vocational Education: A Multiliteracy Pedagogical Framework for Indonesian Maritime Academies - Winarno; Suprobo, Yok; Suranta, Natanael; Wati, Evita Ratna; Mariasa, I Made; Hidayah, Ferro (Tadris: Jurnal Keguruan dan Ilmu Tarbiyah, 2025)
This qualitative study investigates the integration of mental health literacy into Indonesian maritime vocational education through multiliteracy pedagogical frameworks. Despite high prevalence of psychological challenges among seafarers—including isolation, depression, and elevated suicide risk—mental health competencies remain absent from maritime curriculum structures. Through semi-structured interviews and focus group discussions with 42 participants (maritime lecturers, veteran seafarers, and recent graduates), this research examines stakeholder perspectives on mental health literacy needs, multiliteracy pedagogical approaches, lecturer competency requirements, and veteran knowledge integration mechanisms. Findings reveal 92.9% recognition of mental health as critical competency but only 7.1% perceiving adequate curriculum preparation. Case study analysis and veteran testimonial presentations achieve 100% endorsement, while integration into Maritime English courses garners 88.1% support. Significant lecturer competency gaps are identified, particularly in responding to mental health disclosures (2.7-point gap). Results demonstrate that multiliteracy pedagogy offers culturally appropriate, feasible pathways for embedding mental health literacy within existing educational structures. The research provides evidence-based recommendations for BPSDMP curriculum developers and maritime educators regarding professional development priorities, veteran-academy partnership mechanisms, and institutional support requirements for sustainable mental health literacy initiatives that enhance seafarer psychological preparedness and workforce resilience.